Foreign Trade, Foreign Direct Investment and Economic Growth in Nepal - Chhetri, Hom Bahadur (Janapriya Journal of Interdisciplinary Studies, 2022)
One of the important issues that persist in the economic literature is the relationship between foreign trade, foreign direct investment and economic growth in host countries. This issue has become renewed interest in recent years mainly for countries suffering from unemployment problems and lack of technological progress. This paper analyzed this issue for Nepal using time series data over the period of 1995-2020.The ARDL bound test approach to co-integration has been used to analyze long-run and short-run relationship between variables. The study found that there is a co-integration between foreign trade, FDI and economic growth. The study also found that there is a strong positive interaction between foreign trade and FDI in progressing economic growth both in the short-run and long-run. The results show that the foreign trade and FDI can play a significant role to accelerate the economic growth of Nepal.